Parametric Optimization of GTAW welded ASTM A192 Boiler Tubes Using Response Surface Methodology (Pakistan Journal of Scientific Research, 2025)
Heavy Mechanical Complex Taxila (HMC) has long struggled with inconsistent weld quality rates on ASTM A192 boiler tubes. To resolve these challenges, this study employs Response Surface Methodology (Central Composite Design) to systematically optimize Gas Tungsten Arc Welding (GTAW) parameters, together with a controlled pre-heating routine to ensure uniform microstructure. A designed experimental matrix explored the effects of welding current, shielding-gas flow rate, and filler-metal selection on tensile strength and hardness. Statistical analysis revealed that a welding current of 153 A, a shielding-gas flow rate of 16.9 L/min, and the use of ER70S-6 filler consistently achieved tensile strengths above the ASTM A192 minimum while producing homogeneous, defect-free welds under shop conditions. Analysis of variance confirmed that this parameter set significantly reduces defect rates and shortens production cycles. This study reveals the range for welding current (140A-160A) and gas flow rate (15-17 L/min) to obtain optimum UTS and Hardness in ASTM A192 GTAW welded joints.
Keywords: Response surface Methodology; Gas Tungsten Arc Welding (GTAW).; Analysis of Variance; Central Composite Design (CCD)